Answer
The solution is $(-1,-4)$.
Check: Both first and second equations are satisfied when we put the solution in the equations.
$-4=3+7(-1)=-4$ and $-4-(-1)=-4+1=-3$
Work Step by Step
Given: $y=3+7x$ and $y-x=-3$.
From the second equation, we have
$y=x-3$. Substituting this in the first equation, we get
$(x-3)=3+7x$
$\implies 7x-x=-3-3$ or $6x=-6$
$\implies x=-1$
Putting the value of $x$ in the first equation, we obtain
$y=3+7(-1)=3-7=-4$.
The solution is $(-1,-4)$.
Check: Both first and second equations are satisfied when we put the solution in the equations.
$-4=3+7(-1)=-4$ and $-4-(-1)=-4+1=-3$